Blood Donation—A Promising Field for Social Marketing - Ioannis, Tagarakis A.; Panagiotis, Tsiapourlianos K.; Eleni, Chatziefstathiadi E.; Panagiota, Kokkori; Vaxevani, Valentina; Georgios, Papazisis; Fani, Tsolaki; Stefanos, Karakolias; Marios, Daskalopoulos; Georgios, Tagarakis I. (International Journal of Social Science Research, 2024)
Blood donation is the donation of blood for the purpose of transfusion and consequently the organization that has undertaken the collection, storage and disposal of blood. The idea of blood donation for the purpose of treatment has existed since the age of medicine. It took many successful and unsuccessful attempts to reach the current state of blood transfusion. Blood tests on the blood donor are a necessary condition, because they ensure the safety of the recipient and, at the same time, can inform the blood donor about the possible possibility of being a carrier of a serious disease. Today, thanks to the development of technology, the separation of whole blood (WB) into derivatives is relatively easy. Transfusion therapy using blood products has significant advantages. Blood donation is different from other altruistic acts, because of the way it is done and because the blood is so personal. In addition, its benefits are not only vital for the recipient, but multiple for the blood donor himself. This paper studies the context of the history of blood donation. The aim of the work is to highlight the special history of blood donation and to determine its progress in the present era.